Youth temporalities and uncertainty: Understanding variations in young Argentinians' professional careers. (November 2018) - Longo, María Eugenia
Social class and the labor market, traditional emphases of sociological analysis, are insufficient to explain variations in modes of professional insertion among young people. Arguing against the dominant understanding of young adults as project-less prisoners of presentism and an uncertain labor market in Argentina, this article reveals the existence of multiple forms of youth temporalities underlying the ways in which young adults are able (or not) to project themselves into the future and enter the working world. Drawing from longitudinal qualitative data, I have identified four types of youth temporalities: planners, executers, dormants and opportunists. This typology brings variation to the way subjects experience time and how this experience helps to examine career choices, thereby opening a new analytical path that connects with broader analyses of dominant temporal frames of professional insertion.